Evaluation of Thymus vulgaris aqueous extract as a natural antimicrobial agent against urinary tract infection pathogens - ABASS, Hashim; AL-MAHDAWI, Muthanna Abdlkhader Salh; CHALLOOB, Mohammed Sabea; ABED, Hayder (One Health & Risk Management, 2025)
Introduction. Urinary tract infections (UTIs) are often caused by bacteria such as Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) which can lead to major health problems. The purpose of this study was to to examine the antibacterial effects of extract of Thymus vulgaris aqueous against these uropathogens. Materials and Methods. The aqueous extract of Thymus vulgaris was prepared via hot water decoction (yield: 3.6 g from 30 g dried plant material 12%). Bacterial strains were isolated from 25 clinical urine samples and identified using selective culture media using the Gram staining and biochemical characterization. Antibacterial activity was assessed by using the agar well diffusion method with extract concentrations (50, 100 and 200 mg/mL) of Thymus vulgaris extract. Results. The results of this study showed dose dependent of inhibition zone with S. aureus showing greater susceptibility (ZOI: 10–27 mm) compared to E. coli (ZOI: 9–23 mm). Ciprofloxacin shown larger inhibition zone (28–30 mm). Conclusions. These findings demonstrate promising antibacterial potential of T. vulgaris aqueous extract as a natural alternative to combat antibiotic-resistant UTIs. These results support previous investigation about T. vulgaris as an alternative or complementary treatment for bacterial infections.